Green Synthesis of Magnetic Adsorbent Using Groundwater Treatment Sludge for Tetracycline Adsorption. (October 2019) - Qu, Zhan; Wu, Yaqiong; Zhu, Suiyi; Yu, Yang; Huo, Mingxin; Zhang, Leilei; Yang, Jiakuan; Bian, Dejun; Wang, Yi
Abstract: Groundwater treatment sludge is an industrial waste that is massively produced from groundwater treatment plants. Conventional methods for treatment of this sludge, such as discharge into deep wells or the sea, or disposal at landfills, are not environmentally sustainable. Here, we demonstrate an alternative strategy to recycle the sludge by preparing a magnetic maghemite adsorbent via a one-step hydrothermal method with NaOH solution as the only solvent. With this method, the weakly magnetized sludge, which contained 33.2% iron (Fe) and other impurities (e.g., silicon (Si), aluminum (Al), and manganese (Mn)), was converted to magnetic adsorbent (MA) with the dissolution of Si/Al oxides (e.g., quartz and albite) into the liquid fraction. At a NaOH concentration of 2 mol·L −1, approximately 18.1% of the ferrihydrite in the Fe oxides of the sludge was converted into 11.2% maghemite and 6.9% hematite after the hydrothermal treatment. MA2 (i.e., MA produced by a 2 mol·L −1 NaOH concentration) exhibited a good magnetic response of 8.2 emu·g −1 (1 emu = 10 −3  A·m 2 ), and a desirable surface site concentration of 0.75 mmol·g −1 . The synthesized MA2 was used to adsorb the cationic pollutant tetracycline (TC). The adsorption kinetics of TC onto MA2 fitted well with a pseudo-second-order model, and the adsorption isotherms complied well with the Langmuir model. The maximum adsorption capacity of MA2 for TC was 362.3 mg·g −1, and the main mechanism for TC adsorption was cationic exchange. This study is the first to demonstrate the preparation of an MA from recycled sludge without a reductant and/or exogenous Fe source. The prepared adsorbent can be used as a low-cost adsorbent with high capacity for TC sorption in the treatment of TC-containing wastewater.